Synthesis and properties of monophospha‐ and diphosphacyclodiynes - Popp, Ralf; Gleiter, Rolf; Rominger, Frank (European journal of organic chemistry, 2018)
The synthesis and structural investigation of a number of monocyclic alkyne systems with one or two phosphorus atoms in the scaffold are presented. The phosphorus centers in these cycles are stabiliz...